2021
DOI: 10.2147/ijgm.s341076
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Cancer Analysis of the Oncogenic Role of Integrin Beta4 (ITGB4) in Human Tumors

Abstract: Background Integrin beta4 (ITGB4) is a transmembrane receptor that plays a key role in tumorigenesis and tumor development. However, there are no pan-cancer analyses of ITGB4. Methods This study demonstrates the first potential oncogenic roles of ITGB4 across 33 tumors based on the dataset of the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Results ITGB4 is highly expressed in many cancers, and distinct correlations exist bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“… 30 Moreover, bioinformatics analysis showed that ITGB4 acts as a pan-cancer oncogene in 33 different types of human tumors. 31 ITGB4 overexpression has been associated with venous invasion and decreased overall survival in patients with NSCLC. 32 ITGB4 has also been closely associated with other respiratory diseases, including spontaneous inflammation of the lungs, airway inflammation and hyperreactivity, and acute lung injury.…”
Section: Discussionmentioning
confidence: 98%
“… 30 Moreover, bioinformatics analysis showed that ITGB4 acts as a pan-cancer oncogene in 33 different types of human tumors. 31 ITGB4 overexpression has been associated with venous invasion and decreased overall survival in patients with NSCLC. 32 ITGB4 has also been closely associated with other respiratory diseases, including spontaneous inflammation of the lungs, airway inflammation and hyperreactivity, and acute lung injury.…”
Section: Discussionmentioning
confidence: 98%
“…The exosomal miR-105 secreted by breast cancer (BC) targets MXI1, activates the MYC pathway in CAFs, enhances the glycolysis and glutamine decomposition of CAFs, and detoxifies the metabolites (lactate and NH4 +) to fuel adjacent cancer cells [238]. ITGB4 is highly expressed in various cancers and contributes to tumor progression [272]. Studies on triple-negative breast cancer (TNBC) found that cancer cell-derived exosomal ITGB4 could be delivered to CAFs to induce BNIP3L-dependent mitophagy and lactate production in CAFs.…”
Section: Exosomal Cargos Induce Metabolic Reprogramming Of Cafsmentioning
confidence: 99%
“…Transmembrane proteins on the surface of TNBC-EVs also contribute to the metabolic reprogramming of CAFs. Upregulation of integrin β (ITGB4) is associated with tumor progression [ 124 ]. Interestingly, ITGB4 is not expressed in CAFs, but its expression is induced by contact with TNBC cells [ 125 ].…”
Section: Tnbc-evsmentioning
confidence: 99%